2022
DOI: 10.1002/cbm.2266
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and crime: An exploration of gambling availability and culture in an English prison

Abstract: Background: There is evidence that prisoners have the highest rate of problem gambling in any population, but little is known about the nature of in-prison gambling, the motives for it or how it relates to prior gambling behaviour.Aims: To investigate the prevalence and type of gambling prior to prison and the prevalence, type, and reasons for gambling in prison.Methods: Two hundred and eighty-two male volunteers in a Category B male prison in England completed a questionnaire which included the Problem Gambli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Of the 26 included studies, publication years ranged from 1993 ( Templer, Kaiser, & Siscoe, 1993 ) to 2023 ( Kirchmann-Kallas et al, 2023 ). Studies were conducted in USA ( k = 7; Anderson, 1999 ; Kerber, Hickey, Astroth, & Kim, 2012 ; Templer et al, 1993 ; Walters, 1997 ; Walters & Contri, 1998 ; Westphal & Johnson, 2006 ; Zorland, Kuperminc, Mooss, Gilmore, & Emshoff, 2013 ), Australia ( k = 4; Lahn, 2005 ; Riley & Oakes, 2015 ; Riley et al, 2017 , 2018 ), New Zealand ( k = 3; Abbott, McKenna, & Giles, 2005 ; Abbott & McKenna, 2005 ; Sullivan, Brown, & Skinner, 2008 ), UK ( k = 3; May-Chahal, Wilson, Humphreys, & Anderson, 2012 ; May-Chahal, Humphreys, Clifton, Francis, & Reith, 2016 ; Smith et al, 2022 ), Canada ( k = 2; Turner, Preston, Saunders, McAvoy, & Jain, 2009 , 2012 ), Germany ( k = 2; Kirchmann-Kallas et al, 2023 ; Zurhold, Verthein, & Kalke, 2014 ), and one study each from the following countries: Colombia ( Ruiz-Pérez & Echeburúa, 2019 ), Finland ( Lind, Salonen, Järvinen-Tassopoulos, Alho, & Castrén, 2019 ), Japan ( Yokotani et al, 2019 ), Poland ( Lelonek-Kulela, 2020 ) and Sweden ( Widinghoff et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 26 included studies, publication years ranged from 1993 ( Templer, Kaiser, & Siscoe, 1993 ) to 2023 ( Kirchmann-Kallas et al, 2023 ). Studies were conducted in USA ( k = 7; Anderson, 1999 ; Kerber, Hickey, Astroth, & Kim, 2012 ; Templer et al, 1993 ; Walters, 1997 ; Walters & Contri, 1998 ; Westphal & Johnson, 2006 ; Zorland, Kuperminc, Mooss, Gilmore, & Emshoff, 2013 ), Australia ( k = 4; Lahn, 2005 ; Riley & Oakes, 2015 ; Riley et al, 2017 , 2018 ), New Zealand ( k = 3; Abbott, McKenna, & Giles, 2005 ; Abbott & McKenna, 2005 ; Sullivan, Brown, & Skinner, 2008 ), UK ( k = 3; May-Chahal, Wilson, Humphreys, & Anderson, 2012 ; May-Chahal, Humphreys, Clifton, Francis, & Reith, 2016 ; Smith et al, 2022 ), Canada ( k = 2; Turner, Preston, Saunders, McAvoy, & Jain, 2009 , 2012 ), Germany ( k = 2; Kirchmann-Kallas et al, 2023 ; Zurhold, Verthein, & Kalke, 2014 ), and one study each from the following countries: Colombia ( Ruiz-Pérez & Echeburúa, 2019 ), Finland ( Lind, Salonen, Järvinen-Tassopoulos, Alho, & Castrén, 2019 ), Japan ( Yokotani et al, 2019 ), Poland ( Lelonek-Kulela, 2020 ) and Sweden ( Widinghoff et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( k = 15) assessed gambling problems with the South Oaks Gambling Screen (SOGS) ( Abbott et al, 2005 ; Abbott & McKenna, 2005 ; Anderson, 1999 ; Kerber et al, 2012 ; Lahn, 2005 ; Sullivan et al, 2008 ; Lelonek-Kulela, 2020 ; Templer, 1993 ; Turner et al, 2009 , 2012 ; Walters, 1997 ; Walters & Contri, 1998 ; Westphal et al, 2006 ; Yokotani et al, 2019 ; Zorland et al, 2013 ), some ( k = 4) studies used the Problem Gambling Severity Index (PGSI) measure ( May-Chahal et al, 2012 , 2016 ; Smith et al, 2022 ; Turner, Preston, McAvoy, & Gillam, 2012 ), others ( k = 4) used the Early Intervention Gambling Health Test (EIGHT) ( Riley & Oakes, 2015 ; Riley et al, 2017 , 2018 ; Sullivan et al, 2008 ), and ( k = 3), and some studies ( k = 3) used the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) or DSM-IV-JUNIOR (JR) criteria ( Turner et al, 2012 ; Westphal & Johnson, 2006 ; Widinghoff et al, 2019 ). One study each used the BQPG measure ( Ruiz-Pérez & Echeburúa, 2019 ), the Lie/Bet Questionnaire ( Zurhold et al, 2014 ), BBGS measure ( Lind et al, 2019 ), and KFG ( Petry, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…University of Lincoln pre-sentence reporting, community sentences, post-release supervision, or a combination. This article provides a summary of key findings from a report published by The Howard League entitled '"Surviving, not living": The lived experiences of crime and gambling' (Smith, 2022), with a focus on the lived experience reports of probation interactions. The research (undertaken in 2021) involved semi-structured interviews with 22 people, eighteen of whom were people who had committed crime as a result of gambling and four were family members of people directly impacted.…”
Section: Lauren Smith Lecturer In Psychologymentioning
confidence: 99%
“…Prison populations have consistently been found to include the highest prevalence of problem gambling amongst any population (Adoplhe, et al, 2019;Williams, 2005;) with the prevalence of problem gambling in English prisons found to be 12.1% (May-Chahal et al, 2017). In a recent publication, 45% of participants reported gambling in prison, 28% were categorised as having experienced moderate or problem gambling prior to prison, and 30% reported that gambling was a normal part of prison life (Smith et al, 2022).…”
mentioning
confidence: 99%